Effectiveness of a video-assisted teaching programme on knowledge regarding first aid management among bus drivers: a quasi experimental study - Vinita Pandey; Vartika Trivedi; Ashly; Mehvish Khalid; Diksha Bahuguna; Swati Shukla (International Journal Of Community Medicine And Public Health, 2026)
Background: Bus drivers are frequently the first responders to road traffic accidents and passenger medical emergencies, yet many lack adequate first aid knowledge. A video-assisted teaching programme (VATP) offers a learner-friendly method of improving this knowledge among adult learners with varied educational backgrounds. To assess knowledge regarding first aid management among bus drivers before and after a VATP, and to determine the association between pre-test knowledge and selected socio-demographic variables. Methods: A quasi-experimental one-group pre-test post-test design was used. Thirty-five bus drivers from a selected college in Dehradun, Uttarakhand, were enrolled through purposive sampling. Knowledge was measured using a 28-item structured, expert-validated questionnaire (r=0.78) administered before and after a video-based teaching intervention. Data were analysed using descriptive statistics, the paired t-test, and the chi-square test. Results: Mean knowledge score rose from 13.00 (SD=5.72) pre-test to 19.97 (SD=4.96) post-test, a gain of 6.97 points (t (34)=5.82, p